N-(4-tert-Butylbenzyl)phthalimide - Jiang-Sheng Li; Jim Simpson; Xun Li (Acta Crystallographica Section E, 2009)
The molecule of the title compound [systematic name: 2-(4-tert-butylbenzyl)isoindoline-1,3-dione], C19H19NO2, is V-shaped with a dihedral angle of 74.15 (7)° between the mean planes of the phthalimide unit and the benzene ring. The methyl groups of the tert-butyl substituent are disordered over two sets of positions, with an occupancy ratio of 0.700 (4):0.300 (4). In the crystal, intermolecular C—H...O hydrogen bonds link adjacent molecules into centrosymmetric dimers. An additional weak C—H...O contact, together with weak C—H...π and π–π interactions [centroid–centroid distance = 3.961 (2) Å] generate a three-dimensional network.